Innovation: From small 'i' to large 'I' - Sang M. Lee (International Journal of Quality Innovation, 2018)
Innovation is the lifeline for every organization. The primary purpose of innovation is to apply new ideas or technologies to create new or added value for the organization. This narrow goal is for small 'i'. In the dynamic digital age, however, the goal of innovation should be much more aspirational and noble: 'doing well by doing good' for the society at large and humanity. This lofty goal of innovation is for large 'I'. In this paper, we review the evolution process of innovation and propose how innovation can disrupt the barriers to creating a smart future, the aspirational goal of innovation for the greater good.
Keywords: 650